EDUCATIONAL BOOK DESIGN OF HIJAIYAH LETTERS "PINTAR HURUF HIJAIYAH" FOR ISLAMIC PRESCHOOL-AGE CHILDREN IN DAYEUHKOLOT - Athasania, Aqilah Nadhira; Apsari, Diani; Utami, Lira Anindita (eProceedings of Art & Design, 2024)
It is the obligation of Muslims in Islam to study, read and understand the holy book of the Al-Quran, in order to fulfill the obligation to read to be able to understand the Al-Quran, and of course, we must learn and understand the language used in the Al-Quran, namely Arabic with the alphabetical itself named as Hijaiyah letters. Indonesia has been using the method of learning Hijaiyah letters with the Iqro method created by KH As'ad Humam for a long time, this method uses a module book. However, this learning media Iqro method is a classic one, in which the book contains the Hijaiyah letters in the form of black and white colors only. In this case, learning with the Iqro book is boring for children, reinforced by the results of observations and interviews that preschool-age children (3-5 years) are often bored with this classical method because Iqro is less interesting for them. Moreover, the learning styles of these children are different, some are more suitable with listening methods, some with visuals, some with interactive methods, and others. Therefore, a more interesting and engaging learning media for Hijaiyah letters is needed, which aims to fulfill the obligations of a Muslim and increase knowledge. Keywords: Hijaiyah Letters, Learning Media, Engage, Preschool age children